Learning of The Religion of Islam in Forming The Character of Early Children - Anggradini Puspitaloka, Viny; Najiha, Nasratun; Hibana; Samiaji, Mukhamad Hamid (Islamic Studies Journal, 2022)
The purpose of this study is to explore the impact of Islamic religious learning on the formation of early childhood character . The right learning pattern makes the teaching and learning process fun effectively and efficiently so that they can make a major contribution in shaping their character. what the teacher does without ignoring the child's character with how the learning strategies used by teachers in early childhood education in finding forms of learning in line with the attention of the development of children today who live in the dimension of modernity. Of course, cooperation is needed between the two parties, namely the school and parents in realizing and succeeding in their children's education. This research method uses a literature review, the data that has been collected according to the criteria, then analyzed using a descriptive analysis approach. The results of this study shows that the Islamic religious learning process carried out by teachers by paying attention to the characteristics of children's learning can bridging the formation of children's character towards religious character which has aspect NAM who is strong and has good character, so that later The child will be able to fortify himself from the negative influences that he will get later.